Maternal Haemoglobin and outcome of pregnancy - Amponsah, Kwaku Poku (Department of Obstetrics and Gynaecology, 2022)
Background: The association between maternal haemoglobin concentration and the outcome of pregnancy has been a source of continual controversy. Preterm delivery and low birth weight are major causes of stillbirths and early neonatal deaths. Pre-eclampsia is a major complication which occurs during pregnancy and leads to significant maternal and fetal morbidity and mortality. This study aims to assess the association between maternal haemoglobin concentration and pregnancy outcome. Objectives: To assess the association between maternal haemoglobin concentration and pre-eclampsia, preterm birth and low birth weight. Methods: Retrospective analysis of 191 patients who delivered an infant of 28 weeks gestation or more from 1st to 22nd May 2017 at New Somerset Hospital with documented maternal haemoglobin concentration at 22 – 33 weeks gestation. The maternal haemoglobin concentration used was the lowest documented during 22 – 33 weeks gestation. Main outcome measures: Development of pre-eclampsia, low birth weight and preterm birth. Results: The distribution of pre-eclampsia, low birth weight and preterm birth were skewed towards the higher side of the maternal haemoglobin concentration spectrum. There were statistically significant differences in the development of pre-eclampsia, low birth weight and preterm birth between maternal haemoglobin concentrations =>13g/dl and that of < 13g/dl. Pre-eclampsia was associated with relatively lower birth weight, preterm birth and low placental weight independently of the haemoglobin status. Conclusion: High maternal haemoglobin concentration at 22 – 33 weeks gestation is associated with an increased prevalence of pre-eclampsia, low birth weight and preterm birth.